2011
DOI: 10.1097/ypg.0b013e32834371e8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serotonin transporter promoter and BDNF Val66Met genotype on personality traits in a population representative sample of adolescents

Abstract: The purpose of this study was to investigate the effects of the 5-HTTLPR and brain-derived neurotrophic factor (BDNF) Val66Met polymorphisms on self-reported Big Five personality traits and their facets in a population representative sample of adolescents. The sample consisted of both cohorts of the Estonian Children Personality Behaviour and Health Study, and personality data were collected during its second waves. The 5-HTTLPR and BDNF Val66Met polymorphisms were genotyped. The BDNF Val66Met had a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The 5-HTTLPR ss genotype had a negative impact on mental health after childhood abuse only in patients with the BDNF Val/Val genotype 6. A genegene interaction on conscientiousness in adolescence was found in BDNF Val66Met Met allele carriers, with participants with the 5-HTTLPR ss genotype having the lowest conscientiousness scores 32. These studies support that a 5-HTTLPR and BDNF Val66Met gene-gene interaction plays a role on the phenotypes related to mood disorders and personality.…”
Section: Discussionmentioning
confidence: 51%
“…The 5-HTTLPR ss genotype had a negative impact on mental health after childhood abuse only in patients with the BDNF Val/Val genotype 6. A genegene interaction on conscientiousness in adolescence was found in BDNF Val66Met Met allele carriers, with participants with the 5-HTTLPR ss genotype having the lowest conscientiousness scores 32. These studies support that a 5-HTTLPR and BDNF Val66Met gene-gene interaction plays a role on the phenotypes related to mood disorders and personality.…”
Section: Discussionmentioning
confidence: 51%
“…Nonetheless, there is evidence, albeit mixed, of potential different central nervous system characteristics between those low and high in conscientiousness, which may suggest there may be a specifically biological explanation for the observed effects. Specifically, Hiio and colleagues (Hiio et al, 2011) reported that low conscientiousness is a characteristic of carriers of the brain-derived neurotrophic factor (BDNF) Val66Met genotype Met-allele and several studies have shown that the BDNF Met allele has been associated with an impairment in extinction learning in both mice (Soliman et al, 2010; Yu et al, 2009) and humans (Soliman et al, 2010), likely because of reduced ventromedial prefrontal activity and increased amygdala activity during extinction. Importantly, Yu and colleagues documented that this extinction learning deficit exhibited by BDNF met mice can be reversed by the administration of DCS (Yu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Also epistasis effects between gene variants have to be considered, for example between the 5‐HTT , MAOA and DRD4 genes . Epistasis effects between variants of the 5‐HTT and BDNF genes have also been shown both in animal experiments (reviewed by, and in humans regarding the degree of neuroticism . For instance, Grabe et al .…”
Section: Studies On Humans With Some Focus On the Serotonergic Systemmentioning
confidence: 99%
“…[147][148][149] Epistasis effects between variants of the 5-HTT and BDNF genes have also been shown both in animal experiments (reviewed by, 150 and in humans regarding the degree of neuroticism. 151 For instance, Grabe et al 152 showed that, depending on the genotype of BDNF, which mediate neuronal plasticity, the 5-HTTLPR s allele showed either protective or risk properties with regard to depressive symptoms. Finally, a recent study of adolescents, aged between 17 and 18 years, showed that the 5-HTTLPR, MAOA-uVNTR and BDNF Val66Met genotypes interacted with each other, and with family conflict and sexual abuse to increase the likelihood of delinquency, and with a positive parent-child relationship to decrease the risk of delinquency.…”
Section: Studies On Monkeysmentioning
confidence: 99%